(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
It is known that nursing care is important in the treatment of any disease. Today, the largest number of employees in the field of health care in the world are secondary medical workers. Their work is of great importance in the healthcare sector, not because of their large numbers, but because they provide a wide range of safe, effective and quality medical care to clients.